Lipid Profile and Correlation to Cardiac Risk Factors and Cardiovascular Function in Type 1 Adolescent Diabetics from a Developing Country. (12th May 2014) - Dabas, Aashima; Yadav, Sangeeta; Gupta, V. K.
Abstract : Objective . The adverse role of dyslipidemia in predicting cardiovascular outcomes has not been elucidated extensively among type 1 diabetics in the literature. Methods . We assessed dyslipidemia and its correlation to other cardiac risk factors in adolescents with type 1 diabetes. Total thirty type 1 adolescent diabetics were evaluated for their metabolic profile, including serum lipids and echocardiography was performed. Results . The average age of the cohort was 14.3 ± 3.09 yr with disease duration of 5.35 ± 2.94 yr. The mean HbA1C was 8.01%. The mean serum cholesterol, LDL, HDL, and triglyceride were normal. Serum cholesterol was high in patients with longer disease duration (P = 0.011, r = 0.41 ), high systolic blood pressure (P = 0.04, r = 0.32 ), and elevated HbA1C > 8% (P = 0.038, r = 0.33 ). Higher lipid values were associated with poorer carotid artery distensibility (P > 0.05 ) and higher carotid artery intimomedial thickness (cIMT) (P < 0.05 for cholesterol and LDL). Hyperglycemia adversely affected ejection fractions, though serum lipids did not show any significant effect on left ventricular parameters. Conclusions. Dyslipidemia and hyperglycemia can serve as biomarkers for cardiovascular dysfunction in at-risk adolescents with type 1 diabetes. Carotid artery parameters are adjunctive tools which may be affected early in the course of macrovascular disease.